Analisis Perbandingan Brand Equty Dan Strategi Promosi Pada Produk Smartphone Samsung Dengan Oppo - Rizal Angga Setiawan; Muhajirin Muhajirin (JUEB : Jurnal Ekonomi dan Bisnis, 2022)
In the very rapid development of the business world, many companies or entrepreneurs want their products to be known and liked by consumers. Especially in the development of smartphones that are so fast in technology. The use of smartphones in society is very broad, where almost every place exists and has become a necessity, because smartphones can support communication between humans. Among people, the top smartphone brands are Samsung Smartphones and Oppo Smartphones. The purpose of this research is to determine the difference between Brand Equity and Promotional Strategy on Samsung Smartphones and Oppo Smartphones. The sample used is purposive sampling technique and data collection is done quantitatively method. The analytical tool used is the T-test Differential Test with 100 respondents. From the results of the analysis obtained is a comparative analysis of brand equity for Samsung Smartphones and Oppo Smartphones, which are known to have significant differences. And the Samsung Smartphone Marketing Strategy and Oppo Smartphones are known to have no significant differences.